PENGGUNAAN MODEL PROBLEM BASED LEARNING PADA MATERI PERSAMAAN LINEAR DUA VARIABEL UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Dewi Masitoh (Universitas Pakuan, 2021)
THE USE OF PROBLEM BASED LEARNING MODELS ON THE MATERIAL OF LINEAR EQUATIONS OF TWO VARIABLES TO IMPROVE STUDENT LEARNING OUTCOMESThis study aims to describe the improvement of student learning outcomes in determining the value of the variable value of a linear equation of two variables in a real context, as well as the activeness of students in the learning process using the ProblemBased Learning model. The research was conducted at State Junior High School 5 Bogor City involving 35 students in grade 8-C. The research method used is descriptive analytic through Classroom Action Research with data collection techniques using multiple choice tests and observation of student activity. The results of the study using the problem-based learning model can increase the average student learning outcomes from 64.71 to 72.71 in the first cycle and 81.86 in the second cycle. The percentage of students' complete learning outcomes also increased from 34.29% to 62.86% and increased again to 100%. Students are also involved in the learning process by listening to teacher explanations, being active in groups, actively asking questions, and doing teacher assignments. Learning with problem-based learning models provides opportunities for students to find solutions to the problems given so as to improve learning outcomes and student activity.